2015
DOI: 10.1111/aogs.12834
|View full text |Cite
|
Sign up to set email alerts
|

Breech presentation: its predictors and consequences. An analysis of the Hungarian Tauffer Obstetric Database (1996–2011)

Abstract: Breech presentation is a marker of pathological pregnancy and is independently associated with an increased risk of gestational complications. Closer surveillance and appropriate management of pregnancies with breech presentation is warranted to prevent adverse perinatal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 20 publications
(38 reference statements)
6
39
0
4
Order By: Relevance
“…However, these two important pregnancy complications accounted for only 4% of the total population, the adjusted v 2 for linear trend remained very significant at a level of 64, while it was 68 for the entire cohort (p < 0.0001) ( Table 3). On the basis of these data, we conclude that maternal age should be added to the list of risk factor, as also identified by Cammu et al [10] and Zsirai et al [11]. However, the existence of a "linear law" is a new finding, and we may very roughly approximate the reality by memorizing "y¼ 0.1x" (e.g.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…However, these two important pregnancy complications accounted for only 4% of the total population, the adjusted v 2 for linear trend remained very significant at a level of 64, while it was 68 for the entire cohort (p < 0.0001) ( Table 3). On the basis of these data, we conclude that maternal age should be added to the list of risk factor, as also identified by Cammu et al [10] and Zsirai et al [11]. However, the existence of a "linear law" is a new finding, and we may very roughly approximate the reality by memorizing "y¼ 0.1x" (e.g.…”
Section: Discussionsupporting
confidence: 71%
“…Concerning maternal age Cammu et al [10] as well as Zsirai et al [11] confirmed that "on the maternal side: the older the mother, the higher odds for breech presentation" [10]. In the study of Zsirai et al, the incidence of breech presentation was of 2.8% in women <25 [10], we had enough primiparous women (almost 22,000), and also young ones aged from 12 to 18-20 years to split the categories by age of 2 years (instead of 5-year category in the general analysis including also multiparae) ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations